Development of a short and effective shoulder external rotation strength program in handball: A delphi study - Fredriksen, H.; Cools, A.; Myklebust, G. (Physical Therapy in Sport, 2020)
Highlights: • Two shoulder external rotation exercises reached efficacy and adherence consensus.